Pembelajaran Berdiferensiasi Materi Keanekaragaman Hayati Untuk Meningkatkan Antusiasme Belajar Siswa Kelas X - Mediana, Neng Astry (http://jurnal.untirta.ac.id/index.php/JTPPm, 2025)
Differentiated learning is a learning approach to understand and provide knowledge to students according to students' different talents and learning styles. To examine this, research was conducted with the aim of increasing students' enthusiasm for learning in Biology subjects. In examining this enthusiasm, differentiated learning was applied to Biodiversity material. The type of differentiated learning applied is process differentiation and product differentiation according to students' learning styles. To achieve the research objectives, a descriptive approach was used for class X students of SMA Negeri 1 Pontang, Serang Regency. The results of reflection and evaluation show that differentiated learning can provide enjoyable learning by 72%. Therefore, implementing differentiated learning can increase students' enthusiasm for learning about Biodiversity material. The application of differentiated learning can be one solution in meeting students' diverse learning needs so that the expected learning objectives can be realized.